Effects of inflammatory cytokine IL-27 on the activation of fibroblast-like synoviocytes in rheumatoid arthritis - Wong, Chun K (BioMed Central, 2010)
INTRODUCTION: Interleukin (IL)-27 is a novel member of the IL-6/IL-12 family cytokines that are produced early by antigen-presenting cells in T helper (Th)1-mediated inflammation. Elevated expression of IL-27 has been detected in the synovial membranes and fluid of rheumatoid arthritis (RA). METHODS: We investigated the in vitro effects of IL-27, alone or in combination with inflammatory cytokine tumor necrosis factor (TNF)-α or IL-1 β on the pro-inflammatory activation of human primary fibroblast-like synoviocytes (FLS) from RA patients and normal control subjects, and the underlying intracellular signaling molecules were determined by intracellular staining using flow cytometry. RESULTS: Significantly higher plasma concentration of IL-27 was found in RA patients (n = 112) than control subjects (n = 46). Both control and RA-FLS constitutively express functional IL-27 receptor heterodimer, gp130 and WSX-1, with more potent IL-27-mediated activation of signal transducers and activators of transcription (STAT)1 in RA-FLS. IL-27 was found to induce significantly higher cell surface expression of intercellular adhesion molecule (ICAM)-1 and vascular cell adhesion molecule (VCAM)-1 and release of inflammatory chemokine IL-6, CCL2, CXCL9, CXCL10 and matrix metalloproteinase-1 of RA-FLS than that of control FLS (all P < 0.05). Moreover, an additive or synergistic effect was observed in the combined treatment of IL-27 and TNF-α or IL-1 β on the surface expression of ICAM-1 and VCAM-1 and the release of CXCL9 and CXCL10 of RA-FLS. Further investigations showed that the expression of ICAM-1, VCAM-1 and chemokines stimulated by IL-27 was differentially regulated by intracellular activation of phosphatidylinositol 3-OH kinase-AKT, c-Jun amino-terminal kinase and Janus kinase pathways. CONCLUSIONS: Our results therefore provide a new insight into the IL-27-activated immunopathological mechanisms mediated by distinct intracellular signal transductions in joint inflammation of RA.